Enhancing Interaction Flow Modeling Language Metamodels for Designing Features of Rich Internet Applications - Wakil, Karzan; A. Jawawi, Dayang N.; Rachmat, Haris (International Journal of Integrated Engineering, 2018)
Rich Internet Applications (RIAs) became to standard of interactive web applications on the internet fastly. It is a complex application with a rich user interface that distributed the data between client and server also allowing an asynchronous communication between them, but web engineering methods are not able to design and implement these features impeccably. The recent web engineering method is Interaction Flow Modeling Language (IFML) which adopted by Object Management Group (OMG). It has many features for developing interactions in web application compared with other web engineering methods but also has limitation for designing RIA features. In this paper, we enhance IFML method through extension the metamodels by using UML extension mechanism, in which, we define new IFML metamodel and some new elements to cope RIA features designing in data distribution between client and server. The results show that this enhancement enables IFML to develop the new types of web applications efficiently.